PMU based wide area voltage control of smart grid: A real time implementation approach - Musleh, A.; Muyeen, S.M.; Al-Durra, A.; Khalid, H. (2016)
This paper demonstrates a wide area control scheme for voltage regulation in smart grids. The core objective of this work is to create a realistic wide area control (WAC) approach for controlling the voltage in a modern power system. The measurements are collected using phasor measurement units (PMUs) which are optimally placed into the grid via genetic algorithm (GA). The information from each PMU is then used as the feedback for the wide area controller. A flexible AC transmission system (FACTS) device is used as a reactive power compensation tool to demonstrate the use of WAC action to the local area controller. A real time implementation is carried out using Real Time Digital Simulator (RTDS). Furthermore, a Software-in-the-Loop (SIL) system is developed which connects the RTDS simulation to a MATLAB based program. This program receives the PMU measurements from the RTDS and calculates the WAC action which is sent back to the RTDS simulation. Various tests are conducted to demonstrate the usefulness of the wide area control scheme and its reliability. The results show an acceptable behavior of the designed wide area controller.